Wpływ kompleksowej terapii uzdrowiskowej na leczenie zespołu bólowego kręgosłupa lędźwiowo-krzyżowego = The effect of comprehensive therapy Spa for the treatment of pain syndrome the spine lumbosacral - Wójcik, Gustaw; Skalska-Izdebska, Renata; Kolbuszewska, Agnieszka; Szulc, Anna (Journal of Education, Health and Sport, 2016)
Wójcik Gustaw, Skalska-Izdebska Renata, Kolbuszewska Agnieszka, Szulc Anna. Wpływ kompleksowej terapii uzdrowiskowej na leczenie zespołu bólowego kręgosłupa lędźwiowo-krzyżowego = The effect of comprehensive therapy Spa for the treatment of pain syndrome the spine lumbosacral. Journal of Education, Health and Sport. 2016;6(12):71-83. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192324 http://ojs.ukw.edu.pl/index.php/johs/article/view/4035 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 02.12.2016. WPŁYW KOMPLEKSOWEJ TERAPII UZDROWISKOWEJ NA LECZENIE ZESPOŁU BÓLOWEGO KRĘGOSŁUPA LĘDŹWIOWO-KRZYŻOWEGO The effect of comprehensive therapy Spa for the treatment of pain syndrome the spine lumbosacral Gustaw Wójcik1, Renata Skalska-Izdebska2, Agnieszka Kolbuszewska2, Anna Szulc3 1Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej. Wydział Nauk o Zdrowiu i Nauk Społecznych, Katedra Kultury Fizycznej i Fizjoterapii 2Uniwersytet Rzeszowski, Wydział Medyczny, Instytut Fizjoterapii 3Uniwersytet Medyczny w Lublinie, Wydział Nauk o Zdrowiu, Katedra Rehabilitacji STRESZCZENIE Wstęp: Zespół bólowy kręgosłupa lędźwiowo-krzyżowego jest najczęstszą przyczyną dolegliwości bólowych współczesnego człowieka. Dotyczy coraz więcej osób w różnym wieku, szczególnie w krajach wysokorozwiniętych. Dolegliwości te są trudne do zdiagnozowania, a ich przyczyną są liczne zaniedbania takie jak: brak ruchu, zbyt wysokie BMI, nadmiernie przeciążanie kręgosłupa itp. Leczenie polega na stosowaniu zabiegów fizykoterapeutycznych, kinezyterapii, masażu, farmakoterapii. W terapii uzdrowiskowej wykorzystuje się walory otoczenia, klimat, naturalne źródła wody mineralne oraz lecznicze tworzywa naturalne. Istotne znaczenie ma działanie przeciwstresowe. Cel pracy: Celem pracy była ocena kompleksowej terapii uzdrowiskowej, jej wpływu na zespół bólowy kręgosłupa w odcinku lędźwiowo-krzyżowym. Materiał i metody: Badanie przeprowadzono na grupie 31 osób przebywających na leczeniu sanatoryjnym, u których zdiagnozowano zespół bólowy kręgosłupa lędźwiowo-krzyżowego. Grupę kontrolną stanowiło 12 osób również ze zdiagnozowanym zespołem bólowym kręgosłupa lędźwiowo-krzyżowego, ale nie biorących udziału w leczeniu uzdrowiskowym. W celu oceny wpływu kompleksowej terapii uzdrowiskowej posłużono się zmodyfikowanym kwestionariuszem Oswestry oraz skalą bólu VAS. Wyniki: Po zakończeniu leczenia wykazano znaczną redukcję dolegliwości bólowych u pacjentów leczących się w sanatorium: średnia z pomiaru bólu przed leczeniem uzdrowiskowym wyniosła 5, natomiast po jej zakończeniu 2 (przy poziomie istotności p=0,000002). Jakość życia pacjentów wyraźnie uległa poprawie. Wnioski: Analiza wyników wskazuje, że leczenie sanatoryjne znacznie ograniczyło dolegliwości bólowe u pacjentów z zespołem bólowym kręgosłupa lędźwiowo-krzyżowego, przebywających na terapii uzdrowiskowej w porównaniu do grupy kontrolnej. Stwierdzono także, iż zastosowana terapia uzdrowiskowa wpłynęła na zmniejszenie ilości przyjmowanych przez pacjentów środków farmakologicznych. Słowa kluczowe: zespół bólowy kręgosłupa lędźwiowo-krzyżowego, terapia uzdrowiskowa. ABSTRACT Background: Lumbar spine pain syndrome - a cross is the most common cause of pain of modern human. This applies more and more people of all ages, especially in developed countries. These problems are difficult to diagnose, and their causes are numerous neglect such as lack of exercise, too high BMI, excessive overloading, etc. Treatment is based on physiotherapy treatments, physiotherapy, massage, medication. The spa therapy uses values of the surroundings, climate, natural sources of water and natural healing plastic. It is important here antistress effect. Aim: The aim of this study was to evaluate complex spa therapy and its effect on lumbar-cross spine pain syndrome. Material and methods: The study was conducted on a group of 31 people diagnosed with lumbar-cross spinal pain syndrome, they staying on treatment in the sanatorium. The control group also included people diagnosed with lumbar-cross spinal pain syndrome, but not staying on treatment spa. For about the price impact of comprehensive spa therapy was used a modified questionnaire Oswestry and VAS pain scale. Results: After treatment significantly decreased pain in patients receiving treatment in a sanatorium: the average of measuring pain before spa treatment was 5, and after its completion 2 (with a level of significance of p = 0.000002) Conclusion: After analyzing the results, it was found that the sanatorium treatment significantly reduced pain in patients with lumbar-cross spinal pain syndrome, who were on spa treatments compared to the control group. It was also found that the therapy spa influenced the reduction of the patients were taking pharmacological pills. Key words: lumbar spine pain syndrome, sacral therapy spa.